Ask Question
18 February, 23:40

Multiply and simplify. 3 (x2 + 5) (x2 - 5)

+2
Answers (2)
  1. 19 February, 00:22
    0
    3 x^4 + - 75

    Step-by-step explanation:

    Expand the following:

    3 (x^2 + 5) (x^2 - 5)

    (x^2 + 5) (x^2 - 5) = (x^2) (x^2) + (x^2) (-5) + (5) (x^2) + (5) (-5) = x^4 - 5 x^2 + 5 x^2 - 25 = x^4 - 25:

    3 x^4 - 25

    3 (x^4 - 25) = 3 x^4 + 3 (-25):

    3 x^4 - 25*3

    3 (-25) = - 75:

    Answer: 3 x^4 + - 75
  2. 19 February, 01:04
    0
    3 x^4 + - 75
Know the Answer?